(untitled) (Revista Apotheke, 2023)
In the current research, it is predicted that contemporary art may be produced in different places, not only in traditional institutions but also in non-traditional ones. The paper is divided into three sections. Firstly, I relate distinctive poetic experiences throughout my artistic career to intrinsic problems that came out of each context in which the projects were contrived and carried out. Secondly, I suggest that all projects mentioned in this study show great potential for reflection on new ways of dealing with artistic productions employing collaboration. Finally, I discuss that the place of artistic production and the exhibition of visual arts nowadays interfere directly with the possibilities of collaborative agency strategies as a poetic tool. In this sense, in addition to art galleries and museums, art studios and classrooms may also be considered important places to produce and present contemporary art.